Description of cardiovascular remodeling parameters and osteopontin plasma level in dynamics of the candesartan therapy in patients with chronic kidney disease on the stage before dialysis - V. A. Vizir; O. G. Ovska; A. S. Sadomov (Zaporožskij Medicinskij Žurnal)
Aim. To examine the cardiovascular remodeling parameters and osteopontin plasma level in dynamics of the candesartan therapy in patients with chronic kidney disease on the stage before dialysis